For a temporal ecology of rush-hours: a survey of choices of work hour in the Paris region - Emmanuel Munch (Université des Sciences et Technologies de Lille, 2021)
Today an ever-increasing proportion of the French working population has access to working hours that are no longer subject to the explicit diktat of the employer. However, in Île-de-France (Paris region), the problems of congestion in the morning rush-hour continue to intensify. Thus, before trying to solve peak congestion problems, we need to understand the underlying reasons on which an individual’s work schedule choices are based. Why does a worker with flexible work hours commute during rush-hour? Our research adopts a comprehensive approach and focuses on daily scheduling demands. It relies on the results of a survey (3202 respondents) and interviews (29). Respondents and interviewees are executives from the Plaine Saint-Denis area. To describe temporal strategies that explain voluntary commuting during peak hours, we organize our hypotheses along three dimensions:(I) There remain constraints faced by couples (school hours, meeting hours), which force workers with flexible hours to go to work during peak hours. (II) Workers with flexible hours and fewer couple-related constraints prefer to arrive before or during the rush-hour (late afternoon leisure time, activities with family and friends). (III) There are social norms regarding work hours (the ideal of the disciplined worker or the dedicated executive), which limit flexibility by frowning on those who arrive overly late at the office. In conclusion, by revealing the organic intricacy of work synchronisation, our article generates operational recommendations for reducing congestion at peak hours.